Temperature driven changes in the diet preference of omnivorous copepods: no more meat when it's hot?. (16th November 2015) - Boersma, Maarten; Mathew, K. Avarachen; Niehoff, Barbara; Schoo, Katherina L.; Franco‐Santos, Rita M.; Meunier, Cédric L.
Abstract: Herbivory is more prevalent in the tropics than at higher latitudes. If differences in ambient temperature are the direct cause for this phenomenon, then the same pattern should be visible in a seasonal gradient, as well as in experiments manipulating temperature. Using 15 N stable isotope analyses of natural populations of the copepod Temora longicornis we indeed observed seasonal differences in the trophic level of the copepod and a decrease in trophic level with increasing temperature. In a grazing experiment, with a mixed diet of the cryptophyte Rhodomonas salina and the heterotrophic dinoflagellate Oxyrrhis marina, T. longicornis preferred the cryptophyte at higher temperatures, whereas at lower temperatures it preferred the non‐autotrophic prey. We explain these results by the higher relative carbon content of primary producers compared to consumers, in combination with the higher demand for metabolic carbon at higher temperatures. Thus, currently increasing temperatures may cause changes in dietary preferences of many consumers.